Metal–ligand cooperation behaviour of Fe and Co complexes bearing a tetradentate phenanthroline-based PNNP ligand. Issue 22 (31st March 2021) - Nakajima, Yumiko; Takeshita, Tomohiro; Jheng, Nai-Yuan
Abstract : A metal–ligand cooperation (MLC) behavior was investigated using Iron and cobalt complexes bearing a phenanthroline-based meridional PNNP ligand, demonstrating a unique long-range MLC, where the phenanthroline backbone behaves as a H2  reservoir. Abstract : This perspective article describes the synthesis of a series of Fe and Co complexes coordinated with a phenanthroline-based meridional PNNP ligand (2, 9-bis((diphenylphosphino)methyl)-1, 10-phenanthroline). PNNP–iron(ii ) dichloride and –cobalt(i ) chloride, [FeCl2 (PNNP)] and [CoCl(PNNP)], underwent abstraction of the benzylic H-atom upon treatment with NaO t Bu, forming the corresponding deprotonated products [FeCl(PNNP′)] (1 ) and [Co(PNNP′)] (2 ), respectively, each of which bears an asymmetrical PNNP′ ligand with a dearomatized phenanthroline backbone as a good metal–ligand cooperation (MLC) scaffold. Complex 2 achieved facile H–H bond cleavage mediated by unique long-range MLC, where the PNNP backbone acts as a H-atom reservoir.